Integrated Public Health and Nursing Approaches in the Prevention and Management of Dental Trauma in Children: A Multidisciplinary Perspective - Alsaeed, Ola Omar; Fahad Mana Almani; Abdulilah Ibrahim Alabdullatif; Abdullah Sultan Alotaibi; Waleed Saud Jeleudan; Munirah Fatis Alshahrani; Abeer Kheder Albishi; Badrieah Saud N Alesaimi; Amjad Mudhayyif Alsufyani; Monif Dhaher Thani Almutrafi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Traumatic Dental Injuries (TDIs) are a highly prevalent global public health issue in children, with lifetime rates of 20-30%. These injuries, often affecting the maxillary incisors, can lead to severe complications like pulp necrosis and root resorption, causing lasting functional, aesthetic, and psychosocial consequences that impair a child’s quality of life. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to synthesize a comprehensive, multidisciplinary approach to the prevention and management of pediatric dental trauma, integrating perspectives from dentistry, nursing, and public health to improve clinical outcomes and reduce health disparities. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The review examines the etiology, risk factors, and classification of TDIs using International Association of Dental Traumatology (IADT) guidelines. It evaluates diagnostic methods, including traditional clinical exams and advanced perfusion-based technologies like laser Doppler flowmetry and pulse oximetry. Treatment strategies for primary and permanent teeth are analyzed, alongside preventive public health interventions and the psychological impact of trauma. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> TDIs are influenced by age-specific behaviors and socioeconomic factors, with significant disparities in care access. Accurate diagnosis is enhanced by perfusion-based vitality tests, which are more reliable than traditional methods in children. Management is staged and biology-focused, prioritizing pulp preservation in young permanent teeth. Effective prevention requires educational programs for caregivers and school personnel, policy mandates for mouthguards in sports, and digital health tools to guide first responders. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"><span style="background-color: transparent; font-size: 11pt; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline;">Conclusion:<span style="background-color: transparent; font-size: 11pt; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline;"> A coordinated, multidisciplinary strategy that bridges clinical dentistry, nursing, and public health is essential to mitigate the incidence and long-term sequelae of pediatric dental trauma. This integrated approach ensures timely intervention, equitable access to care, and improved psychosocial and functional outcomes for children worldwide.